Digitaliseret digtlæsning. Om nogle muligheder i internetbaseret litteraturformidling med Gustaf Munch-Petersens forfatterskab som eksempel - Gertsen, Martine Cardel (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
The article discusses the considerations behind the content and design of a test website dealing with the Danish author and artist Gustaf Munch-Petersen (1912-1938). The website, which can be visited at address http://www.kb.dk/proto/gmp/, is the result of a research and development project at the Royal Library, Copenhagen, the purpose of which is to examine various ideas for presenting Danish literature over the Internet which exploit that medium’s special characteristics. The medium bears within itself a number of opportunities, both for summarising an author’s production and for assisting the reader’s understanding of individual texts. The website tests certain of these opportunities on the basis of a specific author taking as target group the teachers and students of Danish in Danish upper secondary schools. Inspiration for the content and design of the website derives in part from an initial exploratory interview survey of this target group which aimed at uncovering their needs and desires relating to Danish literature on the Internet. The website is based on two main ideas, each of which in its own way seeks to facilitate the reader’s understanding and interpretation of the literature, namely thematisation and contextualisation. With regard to the former, eight theme lines have been drawn through Gustaf Munch-Petersen’s collected works. These are: “Emancipation and the clash of generations,” “Women and love,” “Bourgeoisie and the working class,” “Revolution,” “To be an artist,” “The primitive,” “Dreams and the unconscious” and “The mystical experience.” These theme lines give a general impression of important topics in the author’s work, and enable readers to concentrate their reading on one or more of them while offering certain hints for interpretation. With regard to the latter idea, the texts have been provided with various types of context: explanatory or perspectivecreating material in words or images. These cover explanations of words, a time line showing critical events in the author’s life, cultural life and contemporary society, Gustaf Munch-Petersen’s paintings and drawings, his letters and manuscripts, relevant quotations from other texts, and finally reviews and other press articles on the author. It is shown how thematisation and contextualisation on the website can contribute to what the reader can draw from Gustaf Munch-Petersen’s texts. This is done both by examining the course of one of the eight theme lines, “Women and love”, and by showing how the contexts can give rise to different interpretations in certain of the poems, taking “til en” and “det underste land” as the main examples. Finally future applications and ideas for future development of the website are discussed.